Making monsters: the uncanny power of dehumanization - Smith, David Livingstone (Harvard University Press, 2021)
Preface: Something like a darkness -- What is dehumanization? -- Dehumanization is real -- In the blood -- Essential differences -- The logic of race -- Hierarchy -- The order of things -- Being human -- Ideology -- Dehumanization as ideology -- Ambivalence -- Making monsters -- Last words and loose ends.